Analysis of Factors Affecting Dividend Policy - Wenny Anggeresia Ginting (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2018)
Dividend policy is the company's decision to pay part or all of the profits earned to shareholders specified in the GMS (General Meeting of Shareholders). The independent variables in this study are net profit (profitability) measured through ROE, cash flow and debt (leverage) as measured through DER. While the dependent variable in this research is dividend policy measured by DPR. The purpose of this research is to test and analyze whether ROE, cash flow and DER have significant influence to DPR on Service and Investment Company listed in Indonesia Stock Exchange period 2012-2014. This study uses secondary data with documentation study method in the form of annual financial statements of the company from 2012-2014. The approach used in this research is quantitative with purposive sampling sampling method. Of the 60 companies, only 17 companies were selected to meet the criteria for sampling. Data analysis technique used is multiple linear regression. The value of R Square (RÂ²) is 0.328 which indicates that the variation of dividend policy variables can be explained by variation of net income, cash flow, and debt variable by 32.8%. The results showed that simultaneously net income, cash flow and debt have a positive and significant impact on dividend policy. Partially net profit (profitability) has no significant effect on dividend policy, cash flow has positive and significant influence to dividend policy, and debt (leverage) have a significant effect on dividend policy.Keywords : Profitability; Cash flow; Leverage; Dividend Policy